Perancangan Webcomic Interaktif "Horror Stories Of Indonesia" - Anggie Putiamary; Alvanov Z. Mansoor (Wimba : Jurnal Komunikasi Visual, 2015)
In Indonesian culture, fear is one concept that can be found in traditional folklore which can be seen from various mystical stories from all around the archipelago with implicit moral message. In popular culture, ghost themed folklore then adapted in various media. At the presentation, folklore adaptation medium is closely related with ways to tell tales, or storytelling. One of the effective way in delivering content of a story is by including readerâs interest in a storyline. For example, by using such storyline, or even adding elements that can attract readerâs attention, so the readers may gain different experience in story reading, especially those including visual element. In further development, horrorâthemed popular media faces sour response from audience as they fail to present interesting horror content despite the richness of local culture. Meanwhile, as one of the product of media digitalization, webcomic is a form of comic published in a website that can be accesed online. Some Indonesian webcomic sites has enough attention from the readers, but in the content, the comics are still using printed comic visualization standards, which is accessing page by page, and still not using website format content that is more flexible in visualization design and more interactive for readers. Seeing the condition, experiment of using webcomic in translating the sensation we get from horror genre has potential to lift supernaturalâthemed folklore culture in Indonesia. Horror stories can be presented as an immersing reading experience using website as a wideworld accesible platform. Mulltimediaâs role, such in webcomic is hoped to give novelty in visual narration and also adding insights through the unique side of Indonesian culture. Keywords: folklore, horror, storytelling, webcomic